Объяснение:= b2 - 4ac = 92 - 4·2·10 = 81 - 80 = 1
x1 = -9 - √1 2·2 = -9 - 1 4 = -10 4 = -2.5
x2 = -9 + √1 2·2 = -9 + 1 4 = -8 4 = -2
D = b2 - 4ac = 172 - 4·1·0 = 289 - 0 = 289
x1 = -17 - √289 2·1 = -17 - 17 2 = -34 2 = -17
x2 = -17 + √289 2·1 = -17 + 17 2 = 0 2 = 0
D = b2 - 4ac = 82 - 4·5·(-4) = 64 + 80 = 144
x1 = -8 - √144 2·5 = -8 - 12 10 = -20 10 = -2
x2 = -8 + √144 2·5 = -8 + 12 10 = 4 10 = 0.4
D = b2 - 4ac = (-2)2 - 4·7·(-14) = 4 + 392 = 396
x1 = 2 - √396 2·7 = 1 7 - 3 7 √11 ≈ -1.2785534815808857
x2 = 2 + √396 2·7 = 1 7 + 3 7 √11 ≈ 1.5642677672951713
= b2 - 4ac = (-7)2 - 4·1·12 = 49 - 48 = 1
x1 = 7 - √1 2·1 = 7 - 1 2 = 6 2 = 3
x2 = 7 + √1 2·1 = 7 + 1 2 = 8 2 = 4
1. а)Х_1=2 1/2
Х_2=-1 1/2
б)Х_1=9
Х-2=-9
Объяснение:
2.
а)4х^2-4х-15=0
a=4 b=-4 c=-15
D =b^2-4ac
D=4^2-4×4×(-15)=16-240=256=16^2>0
X_1=-(-4)+16/2×4=20/8=5/2=2 1/2
X_2=-(-4)-16/2×4=-12/8=-3/2=-1 1/2
D/4=(4/2)^2-4×(-15)=2^2+60=64=8^2>0
X_1=(2+8)/4=10/4=5/2=2 1/2
X_2=(2-8)/4=-6/4=-3/2=-1/1/2
ответ: Х_1=2 1/2
Х_2=-1 1/2
б)Х^2-9^2=0
Применяем формулу разности квадратов:
(Х-9)(Х+9)=0
Х-9=0
Х_1=9
Х+9=0
Х_2=-9
ответ: Х_1=9
Х_2=-9
1.
Упростить:
=(2×(3×9)^1/2-(3×100)^1/2+(2×9)^1/2)×
×(3^1/2)+(24)^1/2=(2×3×(3^1/2)-10×(3^1/2)+
+3×(2^1/2))×(3^1/2)=
=6×3-10×3+3×(6^1/2)+(4×6)^1/2=
=18-30+3×(6^1/2)+2×(6^1/2)=
=-12+5(6^1/2)
ответ: -12+5(6^1/2)